Assessing Impact of Rural Tourism in Fooman Township from Viewpoint of Rural Community - Ashraf Sajjadi; Fatemeh Ahmadi (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2014)
The main purpose of this research was to assess Impact of Rural Tourism (IRT) from viewpoint of rural community. The research instrument was structural questionnaire with close-ended questions, which validity and reliability was confirmed. The target population in this research, includes all rural people in Fooman township of Gilan province (N=96,778) out of which, a number of 198 people were selected as statistical prototypes in a classification sampling method by using Cochran’s table and finally 194 questionnaires were analyzed. The descriptive findings of this study showed that putting the garbage in rural areas and increasing locally government departments were the main IRT that were stated by respondents. By applying Factor Analysis Technique, IRT in Fooman Township were reduced to nine factors. These five factors expressed nearly 72% of the total variance of the variables mso-bidi-language: A